Behandling av rettskrivingsvariasjon i norske ordbøker og ordlister - Vikør, Lars S. (LexicoNordica, 2002)
Spelling codification is a governmental responsibility in Norway, allocated to the Norwegian Language Council. The policy of rapprochement between the two official writing standards of Norwegian, Bokmål and Nynorsk, has led to several spelling reforms and an extensive body of optional forms. Partly these forms are considered equal, partly they are grouped in two levels, a main form (or more) to be used in school textbooks and public service, and an optional secondary form (or more) which may be used by pupils in schools and private persons generally. This optionality applies to both the spelling of single words and whole morphological categories, for instance in the choice between two or three genders in Bokmål and the infinitive suffix in Nynorsk, which may be -a or -e. The most important tool for the implementation of this official codification is word lists, produced by private publishers, but needing governmental approval (given by the Language Council) to be allowed in the school system. These lists shall in principle contain all optional forms. But many of these optional forms are rarely used in writing, while forms that are not allowed in the official spelling, may have been accepted as standard forms by many users. The article discusses the treatment of this optionality in three main dictionary types: spelling lists, monolingual definition dictionaries, and bilingual dictionaries.